Ferritinophagy: multifaceted roles and potential therapeutic strategies in liver diseases - Wu, Kejia; Zhao, Wei; Hou, Zeyu; Zhang, Weigang; Qin, Lei; Qiu, Junyi; Wang, Daobin; Zhuang, Lin; Xue, Xiaofeng; Sun, Ding (Frontiers in Cell and Developmental Biology, 2025)
Ferritinophagy, the selective autophagic degradation of ferritin to release iron, is emerging as a critical regulator of iron homeostasis and a key player in the pathogenesis of various liver diseases. This review comprehensively examines the mechanisms, regulation, and multifaceted roles of ferritinophagy in liver health and disease. Ferritinophagy is intricately regulated by several factors, including Nuclear Receptor Coactivator 4 (NCOA4), Iron regulatory proteins and signaling pathways such as mTOR and AMPK. These regulatory mechanisms ensure proper iron utilization and prevent iron overload, which can induce oxidative stress and ferroptosis. In liver diseases, ferritinophagy exhibits dual roles. In liver fibrosis, promoting ferritinophagy in hepatic stellate cells (HSCs) can induce cell senescence and reduce fibrosis progression. However, in non-alcoholic fatty liver disease (NAFLD), chronic ferritinophagy may exacerbate liver injury through iron overload and oxidative stress. In hepatocellular carcinoma (HCC), ferritinophagy can be harnessed as a novel therapeutic strategy by inducing ferroptosis in cancer cells. Additionally, ferritinophagy is implicated in drug-induced liver injury and sepsis-associated liver damage, highlighting its broad impact on liver pathology. This review also explores the crosstalk between ferritinophagy and other selective autophagy pathways, such as mitophagy and lipophagy, which collectively influence cellular homeostasis and disease progression. Understanding these interactions is essential for developing comprehensive therapeutic strategies targeting multiple autophagy pathways. In summary, ferritinophagy is a complex and dynamic process with significant implications for liver diseases. This review provides an in-depth analysis of ferritinophagy’s regulatory mechanisms and its potential as a therapeutic target, emphasizing the need for further research to elucidate its role in liver health and disease.